Different Perceptions of Time Passage Among Older People: A Comparative Study in Terms of Age and Gender - Mohammad Ali Nazari; Sedigheh Forghani Bonab; Jalil Babapour Kheireddin (Sālmand, 2016)
Objectives: The perception of time is a fundamental and complicated cognitive skill, which allows us to perceive a series of events and activities and anticipate some events in the future. The passage of time is influenced by different contributions of the brain regions and basic cognitive processes, especially attention and memory. With regard to changes in the mentioned functions in different ages, this research aimed to determine the differences in time perception between young and older people. Methods & Materials: This causal-comparative study included young (20-30 years) and elderly (60-70 years) women and men living in Tabriz and Marand cities, Iran. The study samples were recruited via convenient sampling method and comprised 64 individuals who were assigned to 2 groups: young (n=30; 15 males and 15 females) and elderly subjects (n=27; 12 males and 15 females). The measurements included mini-mental state examination test, Beck depression inventory, and time reproduction task. At first, the time reproduction task was individually performed for each subject. To prevent fatigue and its impact on time perception, Beck depression inventory and mini-mental state examination test were performed after the time reproduction task. In time reproductiontask, a circle was randomly presented in standard durations of 400, 500, and 600 ms, as short time, andstandard durations of 1800, 2000, and 2200 ms, as long time, successively. In total, 80 trials (40 trials for short times and 40 attempts for long times) were randomly and successively presented. Subjects should hold downthe space key to reproduce similar duration to the stimulus that had been previously presented. The data of all the subjects were analyzed by multivariate analyses test. Results: Our findings showed significant differences between 2 age groups (young and old) with regard to perception variable (P<0.007) in such a way that the older people had shorter reproduction in both short and long time intervals. However, the young people had longer reproduction in short time intervals and shorter reproduction (the time interval of motive existence) in long time intervals. With regard to gender, no significant difference was found between the women and men (P<0.244). Conclusion: Research findings indicate that age affects time perception so that perceived time in the elderly people is shorter than the real physical time. Our findings also showed that if sources pay less attention to the passage of time or the memory capacity declines, the time estimation will be less. Based on cognitive changes in old age, the cognitive abilities of older people were found to decrease with increasing age. As the accurate processing of time intervals relates to memory capacity and attention, the changes in any cognitive process could affect the differences in the perception of time. Probably due to these factors, the reproduction of time in the older people shortens.